Safety and Security in Sudan: Humanitarian Aid Workers’ Risk Perception - Hix,Magdalena (2023)
Protection of humanitarian aid workers (HAWs) is a challenging task. There are various reports on the topic where much research seems to focus on traditional physical attacks and intentional violence against HAWs (security) rather than the accidental event risks (safety) or discussing it separately. These risks are usually defined by the organization’s security risk management holding the power in risk definition and protection measures establishment. This research argues for the need to include humanitarian aid workers’ perception in security risk management to ensure their holistic protection, enabling to bridge the “duty of care to protect” of the latter with the “duty of care to manage own risk” of the former. To explore the research question “What factors influence humanitarian aid workers’ risk perception in Sudan”, the study includes 26 semi-structured in-depth interviews with various humanitarian aid workers based in Sudan. It concludes that it is specific individual heuristics, bringing important views on what these workers value, their inherent biases, and individual and external factors that mutually intersect and influence the humanitarian aid workers’ risk perception. The individual factors (characteristics) here include age, sex (gender), race and ethnicity, nationality, religion, understanding of risk, knowledge, values, and interests. The external factors include country context dynamics, place and time, humanitarian aid worker’s organization and risk information. All of these arguably create the unique risk identity of the humanitarian aid worker needed to be considered, notably in connection with power, whose risk definition and communication count and prevail.
Keywords: Safety; Security; Risk; Risk Perception; Risk Evaluation; Humanitarian (Aid) Worker; Sudan; Protection; Security Risk Management